(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
It is well recognized that certain types of medications for treatment of antihypertensive , known as Calcium channel blockers (CCBs) and calcium ion antagonists are two types of calcium ion antagonists., only work by blocking the free passage of Ca+. Nifedipine, amlodipine, felodipine, diltiazem, and other medications are among them..Fifteen Adult male mice weighing 180-250 gm were randomly divided into three groups and housed at the College of Science’s animal house, where they were fed a regular mice diet of water and pellets ad libitum.. Tthe control group (n=5) were treated with 1ml of distilled water, the 2nd group (n=5) were treated orally with 20 mg/kg body weight of Nifedipine while the 3rd group (n=5) were treated orally with 60mg/kg by oral gavage for 35 days body weight of Nifedipine. The treatment was discontinued for 24 hours before the animals were sacrificed.. The data indicated biochemical parameters alkaline phosphatase (ALP) were found nonsignificant increased in kidney and testicular tissues,but hematological parameters no any variance has been shown in both Hb,PCV,RBC, HCT, MCV, RDW and platelets in all test groups, whereas MCHC did show major increases in both dosage groups of nifedipine, but WBCs count data suggested a decrease in 20mg/Kg dosage only.We showed that nifedipine could reduce lymphocyte counts Substantial increases in monocyte and neutrophil counts were achieved at doses of 60 mg/kg BW when compared to the control group, and significant increases in monocyte and neutrophil counts were achieved at doses of 20 BW when compared to the control group.,Above results indicate that the variations caused by nifedipine drug can have slight negative effects on the parameters of kidney, testis enzymes and hematological parameters.